Electronic Democracy : Using the Internet to Transform American Politics. - Browning, Graeme (Information Today, Inc., 2001)
With a special focus on recent elections, this resource explains the social relevance of online democracy through various case studies. Among the topics explored are the emergence of online voting; how the Internet has drawn youth back into politics and the reinvention of political action; online privacy and how it will affect Internet politics; the common mistakes of Net activists and how to avoid them; and propaganda, hacking, and the dark side of online politics. Also addressed is how the Gore Democrats and the Bush Republicans pushed the Internet envelope during the presidential campaign.